Legal Protection for Creditors on Collateral Rights Not Owned by the Debtor (Case Study of Tuban District Court Decision No. 9/Pdt.G/2020/PN.Tbn) - Eko Muhyani; Fathkurrohman; Sarjiyati; Anik Tri Haryani (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2025)
Abstract Introduction to the Problem: The legal issue arises when collateral rights are pledged in a credit agreement, but the collateral does not legally belong to the debtor. This creates legal uncertainty for creditors and risks the violation of the property rights of the true owner, as exemplified in Tuban District Court Decision No. 9/Pdt.G/2020/PN.Tbn. Purpose/Study Objectives: This article aims to analyze the legal protection available for creditors when collateral used in a credit agreement is not owned by the debtor, and to identify the legal consequences that arise from such circumstances. Design/Methodology/Approach: This study employs a normative juridical method with a case approach, focusing on the Tuban District Court Decision No. 9/Pdt.G/2020/PN.Tbn to examine judicial considerations, the application of legal principles, and the implications for both creditors and third parties. Findings: The analysis shows that creditors face weakened legal certainty and limited rights of execution when the collateral is not legally owned by the debtor. The decision highlights the importance of ensuring the validity of collateral ownership to protect creditors, while also preventing losses for third-party property owners. Paper Type: Research Article.